In vivo overexpression of X-linked inhibitor of apoptosis protein protects against neomycin-induced hair cell loss in the apical turn of the cochlea during the ototoxic-sensitive period - Sun, Shan; Sun, Mingzhi; Zhang, Yanping; Cheng, Cheng; Waqas, Muhammad; Yu, Huiqian; He, Yingzi; Xu, Bo; Wang, Lei; Wang, Jian; Yin, Shankai; Chai, Renjie; et al. (Frontiers in Cellular Neuroscience, 2014)
Aminoglycoside-induced cochlear ototoxicity causes hair cell (HC) loss and results in hearing impairment in patients. Previous studies have developed the concept of an ototoxicity-sensitive period during which the cochleae of young mice are more vulnerable to auditory trauma than adults. Here, we compared neomycin-induced ototoxicity at the following four developmental ages in mice: postnatal day (P)1–P7, P8–P14, P15–P21, and P60–P66. We found that when neomycin was administered between P8 and P14, the auditory brainstem response threshold increase was significantly higher at low frequencies and HC loss was significantly greater in the apical turn of the cochlea compared to neomycin administration during the other age ranges. qPCR data revealed that the expression of apoptotic markers, including Casp3 and Casp9, was significantly higher when neomycin was injected from P8 to P14, while the expression of the X-linked inhibitor of apoptosis protein (XIAP) gene was significantly higher when neomycin was injected from P60 to P66. Because XIAP expression was low during the neomycin-sensitive period, we overexpressed XIAP in mice and found that it could protect against neomycin-induced hearing loss at low frequencies and HC loss in the apical turn of the cochlea. Altogether, our findings demonstrate a protective role for XIAP against neomycin-induced hearing loss and HC loss in the apical turn of the cochlea during the ototoxic-sensitive period, and suggest that apoptotic factors mediate the effect of neomycin during the ototoxic-sensitive period.